Morphological and phylogenetic appraisal of a new Kirschsteiniothelia (Dothideomycetes, Kirschsteiniotheliales) species from Yunnan Province, China - Meng, Qing-Feng; Thiyagaraja, Vinodhini; Worthy, Fiona Ruth; Ertz, Damien; Wang, Xin-Yu; Jayawardena, Ruvishika S.; Fu, Shao-Bin; Saichana, Natsaran (Phytotaxa, 2024)
Kirschsteiniothelia is a saprotrophic genus that occurs in both terrestrial and aquatic habitats. This study introduces a novel species of Kirschsteiniothelia, discovered on the bark of Abies fabri, collected from Yunnan Province, China, and named K. laojunensis. The identification was established through a combination of molecular analyses and morphological characteristics. Kirschsteiniothelia laojunensis is characterized by its large subglobose to globose, black perithecia, clavate, 8-spored asci, fusiform asymmetric ascospores, which are hyaline when immature and become greenish to brown at maturity. This discovery marks the first occurrence of Kirschsteiniothelia on tree bark, with some lichen thallus tissue surrounding the base of the perithecia. Detailed morpho-molecular characterization along with a synopsis table for the genus are provided.